2021
DOI: 10.2174/1570159x18666200831154658
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Ionotropic Glutamate Receptors in the Treatment of Epilepsy

Abstract: Background: A dysfunction in glutamate neurotransmission is critical for seizure. Glutamate is the major excitatory drive in the cerebral cortex, where seizures occur. Glutamate acts via (i) ionotropic (iGlu) receptors, which are ligand-gated ion channels mediating fast excitatory synaptic transmission; and (ii) G proteins coupled metabotropic (mGlu) receptors. Objective: To overview the evidence on the role of iGlu receptors in the onset, duration, and severity of convulsive and nonconvulsive seizures to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 216 publications
(216 reference statements)
0
18
0
Order By: Relevance
“…Since the activation and desensitization kinetics of AMPAR are much faster than those of NMDAR [38], AMPAR antagonists have been focused to prevent ictogenesis and steadily progressive seizure-related brain pathologic plasticity in the epileptic brain [5]. Indeed, AMPAR antagonists terminate SE and seizure activity that are uncontrolled by NMDAR antagonists [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the activation and desensitization kinetics of AMPAR are much faster than those of NMDAR [38], AMPAR antagonists have been focused to prevent ictogenesis and steadily progressive seizure-related brain pathologic plasticity in the epileptic brain [5]. Indeed, AMPAR antagonists terminate SE and seizure activity that are uncontrolled by NMDAR antagonists [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, AMPAR antagonists terminate SE and seizure activity that are uncontrolled by NMDAR antagonists [6][7][8]. Among them, only perampanel is marketed for the treatment of focal epilepsy, which is a novel non-competitive AMPAR antagonist without affecting the NMDAR or kainate receptors [5], although its effects on signaling pathways remain to be elucidated. In the present study, both perampanel and GYKI 52466 ameliorated spontaneous seizure activity in 54% and 50% of animals (responders) in each group, concomitant with the reduced membrane expression of GRIA1 but not GRIA2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the regulation of glutamate receptor activities is one of the major therapeutic targets to inhibit the seizure generation (ictogenesis). Among glutamate receptors, N-methyl-d-aspartate receptor (NMDAR), α-amino-3-hydroxy-5-methylisoxazole-4-propionic acid receptor (AMPAR) and kainate receptor (KAR) have been reported as targets for treatment of epilepsy [8]. Furthermore, the interactions of NMDAR and AMPAR play an important role in synaptic plasticity in the normal brain.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that glutamate levels increase in the extracellular fluid during seizures in temporal lobe epilepsy (TLE) and glutamate can directly activate NMDAR and induce neuroexcitatory toxicity (Albrecht and Zielińska, 2017). Meanwhile, it has been reported that NMDA, AMPA, and kainite (KA) can induce seizures in animal models, and glutamate receptor antagonists inhibit seizures in animals (Celli and Fornai, 2020). In the PTZ-induced status epilepticus (SE), GluN1, GluN2A, and GluN2B subunits are increased and synaptic plasticity impairs in the hippocampus of rats.…”
Section: Introductionmentioning
confidence: 99%